Full TACL database for "Radich" Taisho corpus [data set] - Radich, Michael (Zenode, CERN, 2022)
A full database for use with TACL, a set of tools for computational philological analysis of texts in the Chinese Buddhist canon. For more information about TACL, see here. The corpus associated with this database is a modified version of the Taishō Buddhist canon, as digitised by CBETA.
Gesehen am 12.07.2022
Keywords: Forschungsdaten; Datenbank